Leptospirosis presenting as a flaccid paraplegia. Issue 773 (March 1990) - Mumford, C.; Dudley, N.; Terry, H.
Abstract : A fatal case of leptospirosis in a 64 year old farm worker is described. The dramatic neurological presentation with a rapidly evolving flaccid paraplegia associated with biochemical evidence of renal and hepatic dysfunction is discussed. Attention is drawn to the wide range of neurological symptoms reported in leptospirosis, and to the possibility that this infectious disease may present neurologically.